2016
DOI: 10.5455/msm.2016.28.95-98
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Rule of Halves in Hypertension: an Exploratory Analysis in an Indian Village

Abstract: Introduction:India is a country in transition, the population is graying and the non communicable diseases are rising. In the rural areas of India, the detection of hypertension is poor because of limited healthcare facilities and poor awareness among the people. In one such village, Mirzapur, adopted by the Aligarh Muslim University, there is a planned project to control hypertension in the villages through some innovative approaches. This study was the assessment phase of this project for mass management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
5
10
1
Order By: Relevance
“…Another study conducted in the rural village of Aligarh district of Uttar Pradesh of India reported the awareness regarding hypertension to be 40.3% among adults of more than 40 years. [ 7 ] These two studies from south and north India had concluded that rule of halves is still prevalent in India scenario; however, our study findings are similar as far as the awareness regarding hypertension goes. We found that once a person who is hypertensive comes to the fold of health-care system in Puducherry, on treatment and compliance to treatment increases significantly (at least two-thirds).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Another study conducted in the rural village of Aligarh district of Uttar Pradesh of India reported the awareness regarding hypertension to be 40.3% among adults of more than 40 years. [ 7 ] These two studies from south and north India had concluded that rule of halves is still prevalent in India scenario; however, our study findings are similar as far as the awareness regarding hypertension goes. We found that once a person who is hypertensive comes to the fold of health-care system in Puducherry, on treatment and compliance to treatment increases significantly (at least two-thirds).…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, the proportions of hypertensives started on regular treatment also more in developed countries (70%–85%) compared to developing nations (29%–50%). [ 2 7 13 14 15 16 17 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension and smokeless tobacco use : HTN, an important risk factor for death and morbidity globally, is one of the major causes of ischaemic heart disease, stroke and heart failure 65 66 67 . For developing countries like India, rule of halves 68 , i.e ., half of the hypertensives are undetected, half of those detected are untreated and half of treated are not well controlled is still valid and poses a significant challenge for control of HTN and incident cardiovascular diseases 68 69 .…”
Section: Discussionmentioning
confidence: 99%
“…The 'Rule of Halves' indicates that 50% of the hypertensive cases are undetected; 50% of those detected are not treated, and 50% of those treated are not controlled (15). In support, 17% and 15% of the SOs and MAs in the study were newly diagnosed; and of those detected, 13% and 15% were on treatment for hypertension; and of those treated, 8.8% and 6.6% were currently on treatment.…”
Section: Prevalence Of Hypertensionmentioning
confidence: 70%